Managing health services - Goodwin, Nick (Understanding public health., 2006)
Health care systems are highly complex and dynamic. Different systems around the world vary in the way services are managed yet, regardless of these differences, the need for effective managers and managerial leaders is essential in allowing organizations or professionals to achieve specific goals. This book provides an understanding of the concepts of management, managerial leadership and governance within health care systems. It provides a thorough introduction to, and conceptual framework for, the analysis of health systems management and goes on to examine fundamental management tasks, including: managing income and finances; managing people; managing strategy and change; and, managing results.